Comparison of bacterial communities associated with Xestospongia testudinaria, sediment and seawater in a Singaporean coral reef ecosystem. (2nd April 2018) - Pires, A.C.C.; Cleary, D.F.R.; Polónia, A.R.M.; Lim, S.C.; De Voogd, N.J.; Oliveira, V.; Gomes, N.C.M.
Abstract : Despite alterations caused by anthropogenic activities in Singaporean coral reefs, the sponge communities are quite diverse and Xestospongia testudinaria is one of the most common sponge species. In the present study, we used 16S rRNA gene barcoded pyrosequencing to characterize and compare bacterial communities from different biotopes (sponge, seawater and sediment) and to identify dominant bacterial symbionts of X. testudinaria in a Singaporean coral reef ecosystem. Our results showed that biotope appears to affect the richness, composition and abundance of bacterial communities. Proteobacteria was the most abundant phylum in sediment and seawater whilst Chloroflexi was more abundant in X. testudinaria. Members of the order Caldilineales (fermentation of organic substrates), Chromatiales (purple sulphur bacteria), Rhodospirillales (purple non-sulphur bacteria) and Syntrophobacterales (sulphate-reducing bacteria) were relatively more abundant in X. testudinaria samples.